WRITING SKILL WITH THE ENGLISH SUBTITLE OF THE "FAST AND FURIOUS 9" MOVIE: A CASE OF THE TENTH GRADE STUDENTS OF MA ABADIYAH GABUS-PATI IN ACADEMIC YEAR 2021/2022 - Nira Eko Ambarwati; AB Prabowo Kusumo Adi; Siti Lestari (Wawasan Pendidikan, 2023)
This research focuses on writing skills in narrative text using the "FAST AND FURIOUS 9" movie. In this modern era, educators must have various learning methods so that students can learn comfortably and with fun. Learning through video or movies is considered by the author to be more effective for students. The sample was students of the tenth-grade of MA Abadiyah Gabus-Pati with 26 students. Researchers used experimental research. The instrument of this research is a writing test. Researchers conducted pre-test, treatment and post-test sessions. Data collection was carried out using quantitative methods. Based on data analysis, it showed that the mean of pre-test was 58.5769 while post-test was 69. The T-test showed that sig. (2-tailed) experimental and control groups were 0.000 < 0.05. This means that there are significant differences in student learning outcomes between before and after being treated using the "FAST AND FURIOUS 9" movie. The results of this study indicate that teaching using movies as a medium of learning can improve students' writing skills in narrative texts.